Geriatric Nutritional Risk Index and mortality in individuals with prediabetes and diabetes: a longitudinal cohort study - Qiao, Luyao; Li, Te; Peng, Jiaxing; Xie, Qing; Wu, Mengqian; Li, Yanping; Tang, Zhenyu (Frontiers in Nutrition, 2025)
BackgroundThis study examines the relationship between Geriatric Nutrition Risk Index (GNRI) and all-cause and cardiovascular mortality in individuals with prediabetes and diabetes, aiming to guide clinical nutrition management and extend life expectancy.MethodsWe analyzed a weighted sample of 7,640 individuals with prediabetes and diabetes from the NHANES 2005–2018 and the NCI database. Nutritional status was assessed using the GNRI. Survival outcomes, including all-cause and cardiovascular mortality, were analyzed using Cox proportional hazards regression models and Kaplan–Meier survival curves. Subgroup analyses and restricted cubic spline (RCS) regressions were further conducted to evaluate the robustness and potential nonlinear relationships between GNRI and mortality outcomes.ResultsOver a median follow-up of 8.00 years, 1,210 participants died, including 319 from cardiovascular diseases. Kaplan–Meier curves revealed significantly lower survival rates for both mortalities in participants with low GNRI. Fully adjusted COX regression models revealed a 2.50-fold (95% CI: 2.14–2.92, p < 0.001) increased risk of all-cause mortality and a 2.78-fold (95% CI: 2.04–3.77, p < 0.001) increased risk of cardiovascular mortality in the low GNRI group. These associations remained robust across subgroup analyses. RCS analyses presented nonlinear associations between GNRI and both mortalities (both p-non-linear <0.05, p-overall <0.05).ConclusionGNRI demonstrated a significant, negative, and nonlinear association with all-cause and cardiovascular mortality in US individuals with prediabetes and diabetes, highlighting its utility in improving survival outcomes through nutritional assessment.